The digital future of museums conversations and provocations - Winesmith, Keir.; Anderson, Susan (Susan Jane) (Abingdon, Oxon : Routledge, 2020)
The Digital Future of Museums: Conversations and Provocations argues that museums today can neither ignore the importance of digital technologies when engaging their communities, nor fail to address the broader social, economic and cultural changes that shape their digital offerings. Through moderated conversations with respected and inf luential museum practitioners, thinkers and experts in related fields, this book explores the role of digital technology in contemporary museum practice within Europe, the U.S., Australasia and Asia. It offers provocations and reflections about effective practice that will help prepare today's museums for tomorrow, culminating in a set of competing possible visions for the future of the museum sector. The Digital Future of Museums is essential reading for museum studies students and those who teach or write about the museum sector. It will also be of interest to those who work in, for, and with museums, as well as practitioners working in galleries, archives and libraries.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electronics / Digital; Museums -- Technological innovations; Museums -- Information technology; Digital media; Museums -- Social aspects; Virtual museums; Cultural property -- Digitization